(untitled) (World Bulletin of Public Health, 2025)
Coagulating and immunological status in the central and regional circulation in venous thrombosis of the lower extremities was studied. To determine the state of hemocoagulation and immune status in patients in the morning, blood was taken from the ulnar vein (common crib) and from the femoral vein in the area not affected by thrombosis (regional crib). The assessment of immune status included a study of the relative number of T lymphocytes and their subpopulations. Serum immunoglobulins class A, M, and G were tested